Effects of heat stress and dehydration on cognitive function in elite female field hockey players - MacLeod, H.; Cooper, S.; Bandelow, S.; Malcolm, R.; Sunderland, C. (BMC Sports Science, Medicine and Rehabilitation, 2018)
Background